1996
DOI: 10.1021/jm950877m
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Selectin Blockers. 2. Novel Selectin Blocker as Potential Therapeutics for Inflammatory Disorders

Abstract: As a part of our studies of selectin blockers, we prepared 1-(2-tetradecylhexadecyl)-3'-O-sulfo Le(X) 1 and 1-(2-tetradecylhexadecyl) sLe(X) 2 and examined their inhibitory activities against natural ligand (sLe(X)) binding to E-, P-, and L-selectins. Compounds 1 and 2 were 2 times more potent than the sLe(X) tetrasaccharide toward E-selectin binding and up to 4 times more potent than sLe(X) toward P- and L-selectin binding. Interestingly, compound 1 provided dose-dependent protective effects against an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…4) In the present study, the inhibitory effect of GSC-150 on cancer cell distribution was observed at a lower dose (0.03 mg/mouse, Fig. 3A).…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…4) In the present study, the inhibitory effect of GSC-150 on cancer cell distribution was observed at a lower dose (0.03 mg/mouse, Fig. 3A).…”
Section: Discussionsupporting
confidence: 43%
“…3B), which was comparable with that for the inhibition by GSC-150 (0.28 mM) of specific binding of sLeX to E-selectin. 4) Considering that few KM12-HX cells were attached to non-activated HUVECs (data not shown), the inhibitory effect of GSC-150 shown in Fig. 3B seems to be directed against the cell adhesion molecules expressed on TNF-a-activated HUVECs.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations